Analisis Instrumen Test Sebagai Alat Evaluasi Pada Pembelajaran Di Sekolah Dasar - Titin Sunaryati; Siti Salma Azzahra; Febi Nurul Khasanah; Nadila Dewi; Siti Komariyah (Jurnal Riset Pendidikan Dasar (JRPD), 2024)
In the learning process there is an evaluation carried out by educators to assess the extent to which learning objectives have been achieved, and is used to obtain valid data regarding student development. The benefit of this research is that it can understand that test instruments can measure student understanding, can improve the quality of learning, and can help in evaluating the effectiveness of teaching methods. This research aims to find out that test instruments are part of the evaluation tool for learning. The research uses qualitative research through a literature study approach to deepen understanding of test instrument analysis as an evaluation tool for elementary school learning. The research results show that by using test instruments educators can evaluate learning through student learning outcomes which then educators can use new teaching materials in carrying out learning activities.